2017
DOI: 10.1152/ajprenal.00369.2017
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of NaCl transport mechanisms in the cortical collecting duct

Abstract: The cortical collecting duct (CCD) forms part of the aldosterone-sensitive distal nephron and plays an essential role in maintaining the NaCl balance and acid-base status. The CCD epithelium comprises principal cells as well as different types of intercalated cells. Until recently, transcellular Na transport was thought to be restricted to principal cells, whereas (acid-secreting) type A and (bicarbonate-secreting) type B intercalated cells were associated with the regulation of acid-base homeostasis. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 100 publications
(95 reference statements)
1
14
0
Order By: Relevance
“…Accumulating evidence has demonstrated that renal tubule function, including water reabsorption and urine concentration, is regulated by aquaporins (AQPs) and sodium transporters [ 4 6 ]. AQPs, a family of membrane proteins, play a critical role in regulating water balance [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has demonstrated that renal tubule function, including water reabsorption and urine concentration, is regulated by aquaporins (AQPs) and sodium transporters [ 4 6 ]. AQPs, a family of membrane proteins, play a critical role in regulating water balance [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that endotoxemia decreased AQP2 expression, which is responsible for the decrease of urine osmolality [ 2 ]. In addition, the major fraction of sodium is reabsorbed at the kidney proximal tubule by Na,K-ATPase, apical type 3 Na/H exchanger (NHE3) and Na-K-2Cl cotransporter (NKCC2) [ 6 ]. During endotoxemia, proximal tubular cells, the primary target of endotoxemia, develop abnormal expression or distribution of sodium transporters, leading to impaired sodium reabsorption [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These two pathways originate from principal cells and B-type intercalated cells respectively. In contrast, A-type intercalated can secrete sodium via basolateral Na/K/Cl co-transporter and apical H(Na),K-ATPase (Edwards & Crambert, 2017; Morla et al , 2016). Here we show that sodium reabsorption in CCD from CC-PAN rats is electrogenic and amiloride-sensitive but independent of any ENaC subunit, since none of them is expressed at the apical cell border (Lourdel et al , 2005), revealing the existence of a third pathway for sodium reabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of extracellular Cl − controls the body fluid content of ions, cellular volume, and blood pressure [68]. Likewise, Cl − plays a regulatory role in regulating HCO 3 − absorption and secretion [69] and activity of NBC [70]. NBCe1-B in its resting state is inhibited by high concentrations of intracellular Cl − ([Cl − ] i ) through the Cl − -interacting motif, GXXXP [70].…”
Section: − As a Signaling Ionmentioning
confidence: 99%